INCOME INEQUALITY IN THE URBAN AND RURAL SECTORS OF THE NORTHEAST REGION OF BRAZIL. Issue 2 (July 2015) - Santos, Vladimir Faria dos; Vieira, Wilson da Cruz
<x xml:space="preserve">Abstract</x> In this study, we conduct an analysis of the main determinants of personal income inequality in both urban and rural areas of the Northeast region of Brazil. An earnings equation was estimated and the Shapley value was used in its decomposition. The results show that education and worker experience are the most relevant variables to explain the high index of inequality in earnings in both the rural and urban areas of the Northeast region of Brazil. Moreover, discrimination in the labor market is also an important factor to explain the concentration of income in the rural sector.